THE MODERATION ROLE OF EMPOWERMENT LEADERSHIP IN DIGITAL TRANSFORMATIONAL RELATIONSHIP TOWARDS ORGANIZATIONAL RESILIENCE - Purbiyati, Yuliana Sri; Setyawati, Vincentia Devina; Tjahjono, Monica Candra (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Organizational resilience is a worthy struggle for many organizations. With organizational resilience, the organization can actualize its organizational vision and mission. Apart from that, school organizations can provide learning services, train friendship between students, and provide a sense of security for students. This research was conducted in an elementary school at a foundation on the island of Java with a total of 120 parents of students. This study uses a quantitative approach. The data was processed using the SEM-PLS application. The purpose of this research is to determine the influence of digital transformational relationships on organizational leadership and determine the mediating role of empowering leadership on digital transformational relationships with organizational leadership. The consequence of this research show that digital transform has a constructive and significant sequel on organizational recilience. This research places empowering leadership as a moderating variable in the relationship between digital transformational and organizational leadership. The results found were that empowering leadership did not moderate the relationship between digital transformational and organizational leadership.